Analisis Kesulitan Belajar Mahasiswa Pendidikan Matematika pada Mata Kuliah Analisis Real dengan Sistem Daring - Sari, Ervina Anvita; Hadiprasetyo, Krisdianto; Wulandari, Andhika Ayu (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2021)
The aim of this research to describe the learning difficulties of Mathematic Student on Real Analysis with an Online System. The results of this study expected to be considered making policies to overcome learning difficulties. This research used a descriptive method with a qualitative approach. The researcher used questioner and interview to collect the data. The result of this research showed that the learning difficulties of Mathematic Student on Real Analysis with an Online System were influenced by two factors, they are an internal factor (from the students themselves) and an external factor (from outside of students). The first internal factor that causes learning difficulties is the interesting aspect with a percentage of 64.05% in quite hinder category, and this is because the student chooses real analysis learning, which is actually done face to face. The second internal factor is the motivation aspect, with a percentage of 70.71% in quite hinder category. This is because the student lacks the effort to learn real analysis. The third and fourth internal factors are the talent aspect with a percentage of 50.71% in a hinder category and the philosophical aspect with a percentage of 53.21% in a hinder category. This is because the student assumes that real analysis difficult subjects because the material is in the form of theorems and proofs. The first external factor that caused the learning difficulties is the infrastructure from the family, with a percentage of 64.64% in quite hinder category. This is because students don't have the complete infrastructure to support online learning. The second external factor is the lecturer quality aspect, with a percentage of 71.43% in quite hinder category. This is caused by the speed lecturer delivering learning material. The third external factor is the lecturers' learning method aspect, with a percentage of 58.92% in the hinder category. This is because, in learning, lecturers only use WhatsApp. The fourth external factor is the university facilities aspect, with a percentage of 59.29% in the hinder category. This is because subsidy pulse/quota given to students only a hundred thousand and must be used for 4-5 months of online learning.